Outpatient Registration Information System Design at Lebong Regency Hospital - arifin, ismail; heltiani, nofri; fatolla, devri (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2023)
Lebong Regency Hospital is a Type C hospital that has been operating since 2015. Patient registration services are still manual, where patients register for treatment and are recorded in a register by staff. This results in long queues for services, which impacts patient satisfaction. The objective of this research is to design an outpatient registration information system in an effort to improve services in the registration department. The method used in this research is Microsoft Access software and a MySQL database using a Data Flow Diagram (DFD)-based system development method. The results of this research produce a registration information system to streamline the patient registration process, particularly in the outpatient unit. It is hoped that the hospital will implement the results of the outpatient registration information system design and conduct regular evaluations.